1978
DOI: 10.1021/bi00612a009
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of lateral species separation from phase transitions in nonideal two-dimensional lipid mixtures

Abstract: The two-dimensional statistical mechanical equations necessary to analyze the phase diagram of a nonideal lipid mixture are derived. The Prigogine approximation of the combinatorial term is used in the maximum term of the partition function which contains two parameters that describe the degree of nonideality in the liquid crystal and gel phases. These parameters are used to calculate the mole fraction of like-like and like-unlike lipid interfaces which describe the lateral species separation of like lipids in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 10 publications
2
39
0
Order By: Relevance
“…This model can be outlined as follows. Lipid molecules in binary mixtures are regarded as being either domain segregated, randomly distributed or regularly distributed on a lattice [36]. In the case of regular distribution, the guest molecules tend to be maximally separated because interaction energy between different lipids considerably exceeds that between similar lipids.…”
Section: Resultsmentioning
confidence: 99%
“…This model can be outlined as follows. Lipid molecules in binary mixtures are regarded as being either domain segregated, randomly distributed or regularly distributed on a lattice [36]. In the case of regular distribution, the guest molecules tend to be maximally separated because interaction energy between different lipids considerably exceeds that between similar lipids.…”
Section: Resultsmentioning
confidence: 99%
“…Lateral distribution of lipids in membranes is an important, but not well understood, phenomenon (for reviews, see Jain, 1983;. The components of binary mixtures of lipids can be either phase separated, randomly distributed, or regularly distributed (Von Dreele, 1978). Information on lipid lateral distribution can be deduced from freeze-etch electron microscopy (e.g., Tillack et al, 1982;, fluorescence microscopy (e.g., Haverstick and Glaser, 1987; Rodgers and Glaser, 1991), calorimetry (e.g., Mabrey et al, 1978;Melchior, 1986), spin labels (e.g., Berclaz and McConnell, 1981), the thiolate-disulfide interchange method (Krisovitch and Regen, 1991), and computer simulations (e.g., Jan et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to random distribution and domain formation, Pyr-PC has also been suggested to be regularly distributed in lipid membranes. A regular distribution is a lateral organization where the guest molecules (e.g., Pyr-PC) are maximally separated in the lipid matrix (e.g., DMPC) (Von Dreele, 1978). As shown by Somerharju et al (1985), the plots of E/M versus the mole fraction of Pyr-PC, Xpyrpc, in egg yolk phosphatidylcholine (egg-PC) and in DPPC are not smooth; the plots have several linear regions separated by kinks.…”
Section: Introductionmentioning
confidence: 99%
“…In a statistical mechanical calculation of binary lipid mixtures, von Dreele [32] has found that the non-ideality parameters of DMPC/DSPC are greater than those of the corresponding DMPC/DPPC dispersion. He has also foundcontrary to what is assumed in regular solution theorythat the non-ideality parameters change with the composition of the mixture, especially in the gel phase, as expected i 588 A. Landwehr and R. Winter: The 7; x,p-Phase Diagram of Binary Phospholipid Mixtures from the higher packing density in this phase.…”
Section: Resultsmentioning
confidence: 99%
“…The mixture has also been predicted to display peritectic phase behaviour [30, 3 I]. DTA results, ---: calculation) In a statistical mechanical calculation of binary lipid mixtures, von Dreele [32] has found that the non-ideality parameters of DMPC/DSPC are greater than those of the corresponding DMPC/DPPC dispersion. He has also foundcontrary to what is assumed in regular solution theorythat the non-ideality parameters change with the composition of the mixture, especially in the gel phase, as expected Recently, an extended Monte Carlo computer simulation study applying a ten state Pinks model has been used to describe the phase diagram of two-component phospholipid bilayer membranes of saturated phospholipids [24].…”
Section: Resultsmentioning
confidence: 99%